Oceanside dwelling for Mrs. Clinton Walker, sheet 6, section B-B and details - Frank Lloyd Wight:::::::::
Section drawing which Mills traced from Frank Lloyd Wright's original design for the Walker residence, with additions contributed by Mills for his project on the residence. Includes details on carport, living room, bedroom. Also includes notes on the details.